Development of Interactive Digital Modules to Increase Knowledge of 3-Dimensional Fine Art Creation Material - Syabila, Rifka Komala; Prasetyo, Abdul Rahman (IJESS International Journal of Education and Social Science, 2024)
Cultural arts subject matter on the creation of 3-dimensional applied art works uses a general summary of the material without adjusting the needs of students and integrating technological developments. Students of class XII-E at SMA Negeri 1 Tumpang experience problems in un-derstanding the knowledge material of the creation of 3-dimensional works of art. The solution that can improve students' understanding of the material is the development of flipbook-based interactive digital modules. This research aims to analyze the needs, develop more innovative and interesting digital modules, describe the results of the analysis of the effectiveness of inter-active digital modules in cultural arts subjects on the material of creating 3-dimensional applied fine art works in class XII-E at SMA Negeri 1 Tumpang. The method used in this research is using R&D (Research and Development) with the 4D model by Thiagarajan with 4 stages namely Define (defining), Design (planning), Development (development), and Dissemi-nate (dissemination). The results showed that students need more interactive media. The results of the material and media expert validation trials scored 96% and 90% with very valid criteria. The results of the practicality test of the flipbook-based interactive digital module are feasible to use with 93% module practicality test results with very feasible criteria, and the effectiveness test gets 0.78 if adjusted to the N-Gain Score obtaining high category effective criteria. The criteria obtained indicate that the use of interactive digital modules helps students understand the mate-rial for creating 3-dimensional applied art works very effectively in the learning process.